Hot, flat, and crowded : why we need a green revolution, and how it can renew America - Friedman, Thomas L. (Penguin, 2009)
Examines America's loss of focus and national purpose since 9/11, and the global environmental crisis, and shows how the solutions to these two problems are linked.